2016
DOI: 10.2527/jas.2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Identifying factors contributing to slow growth in pigs

Abstract: Pigs that grow slower than their contemporaries can cause complications for animal welfare and profitability. This study was conducted to investigate factors that may contribute to slow growth of pigs. Pigs ( = 440) farrowed by 65 sows were monitored from birth to market. Pigs were categorized as slow, average, and fast growers based on market weight adjusted to 170 d of age (slow growers were <105 kg, average growers were between 105 and 125 kg, and fast growers were >125 kg). Blood samples were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 44 publications
7
35
0
Order By: Relevance
“…Data from the present study further supports studies reported previously that weight at weaning (and by inference, birth) is a major determinant of lifetime growth performance (e.g., Douglas et al., 2013 , Dunshea et al., 2003 , He et al., 2016 , Smith et al., 2007 , Wolter et al., 2002 ). Pigs weaned heavier at the same age were heavier at every weigh point through to slaughter, with the weight difference between the L and H pigs increasing from 4.1 kg at weaning to 11.7 kg at the end of the finisher period.…”
Section: Discussionsupporting
confidence: 92%
“…Data from the present study further supports studies reported previously that weight at weaning (and by inference, birth) is a major determinant of lifetime growth performance (e.g., Douglas et al., 2013 , Dunshea et al., 2003 , He et al., 2016 , Smith et al., 2007 , Wolter et al., 2002 ). Pigs weaned heavier at the same age were heavier at every weigh point through to slaughter, with the weight difference between the L and H pigs increasing from 4.1 kg at weaning to 11.7 kg at the end of the finisher period.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a disadvantage of an strict AIAO system is the growth variation which is associated with inefficient pen utilisation [8] and poor carcass grading [9]. In this study, 11% of pigs were in flow 3 which is a similar to the percentage of pigs previously reported as slow growing at market age in AIAO systems [10–12]. In an AIAO system, slow growing pigs should only be delayed from the normal production flow ‘off-site’ [2] but this does not always happen in practice and producers need to find alternative management practices that improve productivity without compromising biosecurity and vice versa.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, by delaying pigs from the normal production flow and regrouping them based on BW, producers expect to reduce BW variation and economic loses. However, slow growing pigs require 4 to 6 weeks longer to reach adequate slaughter weights [8] increasing production cost and the possibility of poor carcass grading due to higher fat content [10, 15] and studies have shown that re-grouping slow growing pigs does not improve their growth performance [16, 17] mainly due to the fact that slow growing pigs would still receive the same feed and management practices. Nonetheless, segregating slow growing pigs removes competition from heavier pen mates and offers the opportunity to implement management practices such as greater feeder space and specialise diets that could help to improve their growth performance and reduce the extra time needed to reach adequate slaughter weights.…”
Section: Discussionmentioning
confidence: 99%
“…(1987) demonstrated that weaned piglets offered 9 cm per pig feeder space allowance had significantly higher growth performance compared to those provided 3 cm per pig feeder space allowance. Recently, He et al. (2016) evaluated the effect of restricted feeder space (2 spaces per pen versus 5 spaces per pen; area of each feeding space was 15 cm × 15 cm) on growth performance of weaned piglets.…”
Section: Factors Affecting Feed Intake In Weaned Pigletsmentioning
confidence: 99%